2002
DOI: 10.1023/a:1015443932331
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Children's aggressive behavior and reading difficulties during early elementary school years are risk factors for adolescent problem behaviors such as delinquency, academic failure, and substance use. This study determined if a comprehensive intervention that was designed to address both of these risk factors could affect teacher, parent, and observer measures of internalizing and externalizing problems. European American (n = 116) and Hispanic (n = 168) children from 3 communities who were selected for aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Other intervention studies also have found greater efficacy for boys as compared to girls (Barrera et al, 2002; Flay, Graumlich, Segawa, Burns, Holliday, & Aban, 2004; Komro et al, 2004). The lack of efficacy findings among female students may be accounted for by several factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other intervention studies also have found greater efficacy for boys as compared to girls (Barrera et al, 2002; Flay, Graumlich, Segawa, Burns, Holliday, & Aban, 2004; Komro et al, 2004). The lack of efficacy findings among female students may be accounted for by several factors.…”
Section: Discussionmentioning
confidence: 95%
“…Another preventive intervention focused on primary grade children from three communities, a majority of which were from Hispanic families (Barrera et al, 2002). Students who exhibited aggressive behavior or reading difficulties were randomly assigned to a multi-component intervention or a control group.…”
mentioning
confidence: 99%
“…Although we did not have a control condition for the follow-up period, these data provide preliminary support for short-term durability of treatment effects. Further study is warranted to determine whether PT may produce delayed or sleeper effects with immigrant families where gains in parenting may come slowly and may continue to produce improvements in child behavior over time (Barrera et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the inclusion criterion (80th percentile), but even more by the place of recruitment of the families. Enrollment rates are higher in Incredible Years studies with a high inclusion threshold, e.g., 77% in a study with the 95th percentile CBCL score as inclusion criterion (Barrera et al 2002) and 24% in a study in which the inclusion criterion was a score above the median of the ECBI (Patterson et al 2002). However, in the latter study families were recruited in general practices while in four other studies with high enrollment rates families were recruited at schools (August et al 2001; Barrera et al 2002; Reid et al 2007; Scott et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there are studies that reported decreases in child problem behavior; some studies reported positive effects either on parent or on teacher rated measures (Hutchings et al 2007; Patterson et al 2002), some only on observed child behavior (Brotman et al 2008, 2009; Webster-Stratton 1998), and some on both measures (Barrera et al 2002; Webster-Stratton et al 2001). On the other hand, in several studies the preventive effectiveness of the IY program on child behavior was not demonstrated (Kratochwill et al 2003; Reid et al 2007; Scott et al 2010); no differences between the intervention and control groups on (observed or parent reported) child behavior were found in these studies.…”
Section: Introductionmentioning
confidence: 99%